HALAL CHARACTERISTICS OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) PRODUCTS IN PATEMON VILLAGE, KREJENGAN DISTRICT, PROBOLINGGO REGENCY - Dyah Ochtorina Susanti (Warmadewa Press, 2021)
This research is motivated by the fact that there are still products of Micro, Small and Medium Enterprises (MSMEs) in Patemon Village, Krejengan District, Probolinggo Regency, which do not yet have a halal certificate, because the product does not meet the halal criteria and the public does not understand about the characteristics of halal. This study aims to analyze and provide an understanding about the characteristics of halal, especially on MSME products in Patemon Village, Krejengan District, Probolinggo Regency. The method used in this research is normative legal research with the statute approach, conceptual approach, and comparative approach. The result of this research showed that halal characteristics of MSME products in Patemon Village can be seen from 2 (two) aspects, namely the material and the process of making it or the event to get it. Therefore, it is suggested that the MSME product producers in Patemon Village to immediately take care of their halal product certification and to the government to disseminate information to the public regarding about characteristics of halal on MSME products.